Virtue ethics and cultural competence: Improving service one administrator at a time. (2nd October 2018) - Cram, Bridgette; Alkadry, Mohamad
ABSTRACT: As the United States continues to become more diverse, companies and government agencies face the challenge of ensuring that their workforce is able to serve and to produce products for this diverse population. Public affairs programs also face the challenge of preparing a future public service workforce that is both culturally competent and ethical. This article explores cultural competence in the context of public administration education through a review of why cultural competence and virtue ethics call for similar skill sets and competencies. It concludes with a proposal to integrate cultural competency training and virtue ethics competencies in public affairs programs' curricula.